MiR-21 Is under Control of STAT5 but Is Dispensable for Mammary Development and Lactation - Feuermann, Yonatan (Public Library of Science, 2014)
Development of mammary alveolar epithelium during pregnancy is controlled by prolactin, through the transcription factors STAT5A/B that activate specific sets of target genes. Here we asked whether some of STAT5's functions are mediated by microRNAs. The miR-21 promoter sequence contains a bona-fide STAT5 binding site and miR-21 levels increased in HC11 mammary cells upon prolactin treatment. In vivo miR-21 was abundantly expressed in mammary epithelium at day 6 of pregnancy. Analysis of mice lacking miR-21 revealed that their mammary tissue developed normally during pregnancy and dams were able to nurse their pups. Our study demonstrated that although expression of miR-21 is under prolactin control through the transcription factors STAT5A/B its presence is dispensable for mammary development and lactation.